Pemberdayaan Ibu PKK Desa Sumberwaru Melalui Edukasi dan Pelatihan Penanaman Toga - Chindy Elsa Ramadhani; Tarizza Puspa Anggrelia; Miftahul Maulidiyah; Sovia Maulina Azkiyah; Brelianty Nevy Tyara Chusuma Putri; Abdullah Syafiq Ahmadi; Sari Fatul Layly; Nur Lailatul Maghfiroh; Soffia Dwi Anjani; Salsabilla Dhiya Atik Nuraini; Isna Wulan Mukharomah; Dewi Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Family Medicinal Plants (TOGA) are plants grown in home gardens or small plots for traditional family medicine. In Indonesia, TOGA has significant potential in supporting public health by utilizing local natural resources. The purpose of this empowerment is to improve the knowledge and skills of PKK women in Sumberwaru Village in planting and utilizing TOGA. Using a quantitative approach with a pre-experimental design, specifically a one-group pretest-posttest type, 37 participants, consisting of PKK cadres and women, participated in educational and demonstration activities on TOGA. The pre-test results showed participants' knowledge at 57.29%, while post-test results increased to 96.21%, reflecting a 38.92% improvement. This indicates that the educational program successfully enhanced participants' understanding and skills in planting and utilizing TOGA practically. Based on the research findings, this activity not only increased theoretical knowledge but also provided practical skills that could be applied in daily life, improving family health and economic independence.